SARS-CoV-2 Viral Shedding and Transmission Dynamics: Implications of WHO COVID-19 Discharge Guidelines - Badu, Kingsley; Oyebola, Kolapo; Zahouli, Julien Z. B.; Fagbamigbe, Adeniyi Francis; de Souza, Dziedzom K.; Dukhi, Natisha; Amankwaa, Ebenezer F.; Tolba, Mai F.; Sylverken, Augustina A.; Mosi, Lydia; Mante, Priscilla Kolibea; Matoke-Muhia, Damaris; et al. (Frontiers in Medicine, 2021)
The evolving nature of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has necessitated periodic revisions of COVID-19 patient treatment and discharge guidelines. Since the identification of the first COVID-19 cases in November 2019, the World Health Organization (WHO) has played a crucial role in tackling the country-level pandemic preparedness and patient management protocols. Among others, the WHO provided a guideline on the clinical management of COVID-19 patients according to which patients can be discharged 10 days after the onset of symptoms, with at least three additional days following the resolution of symptoms. However, emerging direct evidence indicating the possibility of viral shedding 14 days after the onset of the symptoms called for evaluation of the current WHO discharge recommendations. In this review article, we carried out comprehensive literature analysis of viral shedding with specific focus on the duration of viral shedding and infectivity in asymptomatic and symptomatic (mild, moderate and severe forms) COVID-19 patients. Our literature search indicates that there is no strong evidence to contradict the current WHO discharge criteria.